2017
DOI: 10.1152/ajpgi.00343.2016
|View full text |Cite
|
Sign up to set email alerts
|

Glycans in the intestinal peptide transporter PEPT1 contribute to function and protect from proteolysis

Abstract: Despite the fact that many membrane proteins carry extracellular glycans, little is known about whether the glycan chains also affect protein function. We recently demonstrated that the proton-coupled oligopeptide transporter 1 (PEPT1) in the intestine is glycosylated at six asparagine residues (N50, N406, N439, N510, N515, and N532). Mutagenesis-induced disruption of the individual -glycosylation site N50, which is highly conserved among mammals, was detected to significantly enhance the PEPT1-mediated inward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 68 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…Therefore, it is expected that deglycosylation at this residue, or alterations in the glycosylation pattern, will positively modulate PEPT1 function (56). However, further investigation suggested that the fundamental role of N -glycosylation at N50 is to protect the extracellular loops from protease degradation in oocytes, and further studies are needed to determine whether this mechanism is consistent in other expression models (57). This finding may mechanistically explain the variability in function between species and tissues (57).…”
Section: N-glycosylationmentioning
confidence: 99%
“…Therefore, it is expected that deglycosylation at this residue, or alterations in the glycosylation pattern, will positively modulate PEPT1 function (56). However, further investigation suggested that the fundamental role of N -glycosylation at N50 is to protect the extracellular loops from protease degradation in oocytes, and further studies are needed to determine whether this mechanism is consistent in other expression models (57). This finding may mechanistically explain the variability in function between species and tissues (57).…”
Section: N-glycosylationmentioning
confidence: 99%
“…Finally, the retentate was lyophilized to obtainthe final sulfated derivate ACW0-Sul. The degree of sulfation (DS), which is the average number of sulfate groups on each sugar residue, was calculated from the sulfur content based on the barium chloride gelatin method [30], using the following formula:DS = 162 × S% (32 − 102 × S%)…”
Section: Methodsmentioning
confidence: 99%
“…The study showed that removal of glycans increased the maximal Gly‐Sar peptide transport rate. In addition, these experiments demonstrated that glycosylation of PepT1 stabilised this transporter against the proteolytic action of trypsine and proteinase K; however, in the case of trypsin, the transporter was stable independently of N‐linked glycans (Stelzl et al ., ).…”
Section: Digestion and Absorption Of Protein And Peptidesmentioning
confidence: 97%
“…Stelzl et al . () investigated the influence of glycosylation on the rate of Gly‐Sar transport. The study showed that removal of glycans increased the maximal Gly‐Sar peptide transport rate.…”
Section: Digestion and Absorption Of Protein And Peptidesmentioning
confidence: 99%